MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR LISTENING PESERTA DIDIK KELAS X IPA 3 SMAN 5 ENREKANG MELALUI PERMAINAN BERBISIK - Mastura, Mastura (JURNAL NALAR PENDIDIKAN, 2020)
AbstractThis study aims to increase the participation and listening learning outcomes of class X IPA 3 SMAN 5 Enrekang students through whispering game techniques. Data obtained from preliminary observations, observations of each cycle of teacher activities, activities and student participation during the learning process, student test results, questionnaire results before and after the application of actions, and structured interview results of students. Data analysis for each round includes data reduction, data exposure, and data inference. The whispering game steps in the listening class are carried out with initial, core, and final learning. The results of this study can improve the learning atmosphere more interesting, lively, and entertaining because learning is centered on students and student participation increases from time to time. The learning outcomes of students' listening increased from the preliminary study to cycle 1, the average value of students became 57.78, in cycle 2 it became 65.83, and in cycle 3 it became 74.72.Keywords: listening, Learning Outcomes, Participation, Whispering Games